Experimental Studies for Small Diameter Grafts in an In Vivo Sheep Model—Techniques and Pitfalls - Eghbalzadeh, Kaveh; Guschlbauer, Maria; Weber, Carolyn; Wacker, Max Theodor; Reinhardt, Stefanie; Djordjevic, Ilija; Sabashnikov, Anton; Maul, Alexandra; Sterner-Kock, Anja; Wahlers, Thorsten C.W.; Scherner, Maximilian; Wippermann, Jens (The Thoracic and Cardiovascular Surgeon, 2019)
Background Scientific attempts to create the “ideal” small diameter vascular graft have been compared with the “search of the holy grail.” Prosthetic material as expanded polytetrafluoroethylene or Dacron shows acceptable patency rates to large caliber vessels, while small diameter (< 6 mm) prosthetic conduits present unacceptably poor patency rates. Vascular tissue engineering represents a promising option to address this problem.Material and Methods Thirty-two female Texel-sheep aged 6 months to 2 years underwent surgical common carotid artery (CCA) interposition using different tissue-engineered vascular substitutes. Explantation of the grafts was performed 12 (n = 12) and 36 (n = 20) weeks after surgery. Ultrasound was performed on postoperative day 1 and thereafter every 4 weeks to evaluate the graft patency.Results The average length of implanted substitutes was 10.3 ± 2.2 cm. Anesthesia and surgical procedure could be performed without major surgical complications in all cases.The grafts showed a systolic blood flow velocity (BFV) of 28.24 ± 13.5 cm/s, a diastolic BFV of 9.25 ± 4.53 cm/s, and a mean BFV of 17.85 ± 9.25 cm/s. Native vessels did not differ relevantly in hemodynamic measurements (systolic: 29.77 cm/s; diastolic: 7.99 cm/s ±  5.35; mean 15.87 ± 10.75). There was no incidence of neurologic complications or subsequent postoperative occlusion. Perioperative morbidity was low and implantation of conduits was generally well tolerated.Conclusion This article aims to give a precise overview of in vivo experiments in sheep for the evaluation of small diameter vascular grafts performing CCA interposition, especially with regard to pitfalls and possible perioperative complications and to discuss advantages and disadvantages of this approach.
Keywords: small diameter grafts; tissue-engineered vascular graft; sheep model